Administration and Content Analysis of Timeout during Volleyball Games - Giazitzi, Κατερίνα; Zetou, Ελένη; Michalopoulou, Μαρία; Aggelousis, Νικόλαος (Inquiries in Physical Education and Sport, 2007)
The aim of the present study was to record the administration of time out in relation to the score, along with coaches analysis of their comments during the time out. Finally the varieties of comments between those teams were recorded depending on which team won and which lost the games. The sample was the 12 coaches of Greek A1 division championships. It was recorded 238 time outs in 12 official games in local period. The procedure was accomplished through video and sound recording during time out and then it was analyzed. The Instrument for Recording Coaches' Comments during Time-Outs (Hastie, 1999) was used. Analysis of frequencies showed that most of the coaches prefer to take time out after the first technical time out (9-16 points -36%) and especially after the second (17-21 points -39.3%). They also used time out mainly when the score is 2 points in favor to the opponent team 22%, when the score is 3 points 18.7% and 18% when the score is 4 points difference. As far as the various kinds of comments that each coach made during time out, it was found that the most of those comments referred to game tactics (50.85%). Psychological comments were fewer (26.70%), and other comments were even less. (19.61%). Finally the technical comments were only (2.84%). Multivariate Analysis of Variance (MANOVA, p<.05) didn’t show any significant difference between the coaches comments and their final ranking (1-4, 5-8, 9-12).